Culture in Translation and Translation of Culture-Specific Items - Hashemi Minabad, Hassan (Iranian Journal of Translation Studies, 2003)
This paper is an attempt to shed light on questions such as culture, translation and the strategies used for translating culture-specific items (CSIs). Examples of culture-specific items are presented following which the strategies and processes developed and employed in order to produce an acceptable translation in the target language of CSIs found in the source language texts will be discussed. The paper concludes presenting instances of extreme adjustment and adaptation of CSIs found in the western literature as were translated by Iranian translators during Qajar Era in late 19th century and early 20th century.